Factors Affecting Customer Satisfaction In E-Commerce - Dina Rahmayanti; Eri Wirdianto; Ikhwan Arief; Arri Fatimah Zahra; Hafizh Ahmad (Jurnal Ilmiah Teknik Industri, 2021)
This research aims to identify the influence of website quality, product quality, product price, and safety shopping on e-commerce customer satisfaction and determine the significant factor influencing e-commerce customer satisfaction. The method used in this research is multiple linear regression analysis to identify the relationship between independent variables and dependent variables. This research uses the purposive sampling technique to determine the sample size through an online questionnaire to obtain the primary data. The 184 respondents respond to the online questionnaire through social media. This research shows that website quality, product quality, product price, and safety shopping simultaneously influence customer satisfaction. Furthermore, the most significant factor affecting customer satisfaction is product quality; this factor contributes as much as 38% among the other three independent variables in this research.